Assessing the effects of endocrine disruptors in the National Children's Study. - Landrigan, Philip (2003)
Children are uniquely vulnerable to toxic chemicals in the environment. Among the environmental toxicants to which children are at risk of exposure are endocrine disruptors (EDs)--chemicals that have the capacity to interfere with hormonal signaling systems. EDs may alter feedback loops in the brain, pituitary, gonads, thyroid, and other components of the endocrine system. They can affect development. Effects of EDs have been described in wildlife populations, in animals exposed experimentally, and to a more limited extent in humans. Mechanisms of action of EDs are increasingly being elucidated, and genetic polymorphisms that convey differential susceptibility to EDs are beginning to be explored. It is hypothesized that in utero and early childhood exposures to EDs may be responsible, at least in part, for decreases in semen quality; increasing incidence of congenital malformations of the reproductive organs, such as hypospadias; increasing incidence of testicular cancer; and acceleration of onset of puberty in females. The National Children's Study (NCS) will provide a unique opportunity to test the validity of these hypotheses in the context of a large prospective multi-year epidemiologic investigation. It will be essential in the NCS to assess exposures to a range of putative natural and synthetic EDs, to assess outcomes possibly due to ED exposure, to examine the potential interplay between EDs and genetic polymorphisms, and to seek links between ED exposures in early life and endocrine, reproductive, neurobehavioral, and other outcomes throughout the life span.